Ngaji, Yuk! : seabrek fadhilah dan kisah inspiratif 58 surat dalam Al-quran /Ibnu Rusydi Al-Anwar; editor Kimya; ilustrator Triastanto S - IBNU RUSYDI AL-ANWAR; Kimya; Triastanto S (Diva, 2014)
267 hlm. ilus 19 cm